Phacoemulsification: an alternative for prophylaxis of a glaucomatous crisis - Stock RA (Dove Medical Press, 2019)
Ricardo Alexandre Stock, Mariéli Wobeto Röhrig, Camila Duranti Mezzomo, Elcio Luiz Bonamigo Medical School of the University of the West of Santa Catarina (Universidade do Oeste de Santa Catarina – UNOESC), Joaçaba, SC, BrazilCorrespondence: Ricardo Alexandre StockMedical School, Universidade do Oeste de Santa Catarina, Belotto Stock Centro Oftalmológico, Rua Rio Branco, 589, Centro, CEP: 89.600-000, Joaçaba, SC, BrazilTel +55 493 522 0788Fax +55 493 522 5059Email ricardostockreal@gmail.comPurpose: To evaluate the effectiveness of phacoemulsification for the prophylaxis of a glaucomatous crisis in the affected and contralateral eyes; to investigate the evolution of intraocular pressure levels after iridotomy and phacoemulsification; to assess the need for antiglaucoma medication after the proposed treatments; and to identify potential complications associated with phacoemulsification.Patients and methods: This retrospective observational study evaluated 22 eyes of 12 patients between September 2006 and September 2018, with a minimum follow-up period of 9 months.Results: After iridotomy, a persistent increase in intraocular pressure was observed in 42.85% of the cases, 100% of the patients required antiglaucoma medications, and recurrence of angle closure was observed in 28.57% of the cases. In contrast, during follow-up of phacoemulsification, the intraocular pressure levels in all eyes evaluated remained normal, without the need for medication, and no recurrence of the glaucomatous crisis or other complications was observed.Conclusion: Phacoemulsification maybe consequently more effective than laser iridotomy for the resolution of angle-closure glaucoma and particularly for preventing its relapses.Keywords: intraocular pressure, glaucoma, angle-closure glaucoma, phacoemulsification